Marketing accountability for marketing and non-marketing outcomes - Kumar, V.; Stewart, David W.; Malhotra, Naresh K. (Bingley, U.K. : Emerald Publishing Limited, 2021)
This latest volume of Review of Marketing Research, Marketing Accountability for Marketing and Non-Marketing Outcomes is divided in three parts: (1) measures of firm performance, (2) measures of social interaction, and (3) measures related to broader societal outcomes such as sustainability and quality of life. Measures of firm performance covered include the marketing implications of financial accounting, customer feedback metrics, drivers of brand equity, brand failure, market orientation capabilities, and multichannel attributions. Measures of social interaction encompass environmental and social performance, social networks, and attitudinal word-of-mouth drivers. The final -- Chapter is devoted to measures related to societal outcomes and focuses on attractiveness of inner city for society. Each -- Chapter presents thought-provoking discussions and new insights which will be relevant to researchers, professionals and students of marketing, branding and consumer behaviour.
Part I. Measures of firm performance -- Chapter 1. An integrative framework for marketing accountability of marketing and non-marketing outcomes / V. Kumar and David W. Stewart -- Chapter 2. The marketing implications of financial accounting / Neil Thomas Bendle, Jonathan Knowles, and Moeen Naseer Butt -- Chapter 3. Customer feedback metrics for marketing accountability / Evert de Haan, Peter C. Verhoef, and Thorsten Wiesel -- Chapter 4. What drives brand equity? A comprehensive study of price and volume premiums / Jianjun (John) Zhu, Thomas S. Gruca, and Lopo L. Rego -- Chapter 5. Do retailers get blamed when manufacturer brands fail? The case for multi-loci attributions and spillover effects / Frank Germann, Ronald L. Hess, Jr., and Margaret G. Meloy -- Chapter 6. Linking market orientation capabilities to organizational performance: A research framework and empirical test / Kåre Sandvik, Karoline U. D. Dahr, and C. Jay Lambe -- Chapter 7. Multichannel data-driven attribution models: A review and research agenda / Ben B. Beck, J. Andrew Petersen, and Rajkumar Venkatesan -- Part II. Measures of social interaction -- Chapter 8. Accountability beyond profitability: Understanding the impact of marketing actions on environmental and social performance / Amalesh Sharma, Sourav Bikash Borah, Anirban Adhikary, and Tanjum Haque -- Chapter 9. A social network research paradigm for marketing: A review and research agenda / Aditya Gupta and Alok R. Saboo -- Chapter 10. The unintended consequences of attitudinal word-of-mouth drivers / Timothy L. Keiningham, Roland T. Rust, Bart Larivière, Lerzan Aksoy, and Luke Williams -- Part III. Measures related to social outcomes -- Chapter 11. What drives inner city attractiveness for society? The role of brick-and-mortar stores / Julian R. K. Wichmann, Thomas P. Scholdra, and Werner J. Reinartz.
Includes index.
Print version record.
Keywords: elektronické knihy; electronic books; Marketing research; Marketing -- Social aspets; Responsibility; Business & Economics -- Marketing -- Research; Market research